1996
DOI: 10.1126/science.274.5294.1859
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Staphylococcal α-Hemolysin, a Heptameric Transmembrane Pore

Abstract: The structure of the Staphylococcus aureus alpha-hemolysin pore has been determined to 1.9 A resolution. Contained within the mushroom-shaped homo-oligomeric heptamer is a solvent-filled channel, 100 A in length, that runs along the sevenfold axis and ranges from 14 A to 46 A in diameter. The lytic, transmembrane domain comprises the lower half of a 14-strand antiparallel beta barrel, to which each protomer contributes two beta strands, each 65 A long. The interior of the beta barrel is primarily hydrophilic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

60
2,394
2
9

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 2,233 publications
(2,465 citation statements)
references
References 45 publications
60
2,394
2
9
Order By: Relevance
“…All three homopolymers exhibited a linear relation between chain length and duration of the blockade. For RNA molecules, the fastest is polyC (∼2 µs/base), poly A is The hemolysin nanopore is shown in cross section, based on the X-ray data of Song et al 19 An ionic current of KCl is driven by the applied voltage through the open pore on the left. Under these conditions, ionic polymers such as nucleic acids are captured by the standing electrical field and driven through the pore.…”
Section: Nanopores As Polymer Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…All three homopolymers exhibited a linear relation between chain length and duration of the blockade. For RNA molecules, the fastest is polyC (∼2 µs/base), poly A is The hemolysin nanopore is shown in cross section, based on the X-ray data of Song et al 19 An ionic current of KCl is driven by the applied voltage through the open pore on the left. Under these conditions, ionic polymers such as nucleic acids are captured by the standing electrical field and driven through the pore.…”
Section: Nanopores As Polymer Sensorsmentioning
confidence: 99%
“…Song et al 19 reported the crystal structure of R-hemolysin at atomic resolution, and their data were used to prepare the space-filling model shown in Figure 5. The entrance to the channel has a diameter of approximately 2.6 nm that contains a ring of threonine residues.…”
Section: What Factors Control Nucleic Acid Movement Through the Hemolmentioning
confidence: 99%
“…[4][5][6][7][8] X-ray crystallographic studies have shown that toxin oligomer complexes most likely assemble in b-barrel or umbrella-like channels in lipid membranes. [9][10][11][12] However, the involvement of such oligomers in cell death is not well understood because most toxin oligomer complexes themselves apparently do not punch holes in membrane and do not simply cause cell death by lysis. 13,14 Instead, the interaction of toxins with cells involves complicated pathways, the end result of which is cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the PAMAM dendrimer and the αHL pore have matching nanoscale dimensions ( Figure 1). 35 Finally, the pore lumen at the trans side is of simple cylindrical shape, which was anticipated to facilitate studying the interaction with PAMAM. In particular, at the trans side, the αHL pore features a cylinderlike transmembrane β-barrel of approximately 2 nm inner width and 5.0 nm height, which narrows to a 1.2 nm-wide inner constriction ( Figure 1A).…”
mentioning
confidence: 99%